Pelatihan Pembuatan Ornamen Dekoratif Suminagashi Pada Media Kain Bagi Gabungan Organisasi Wanita Di Banyumas - Natasia Anggi Laxmita; Yohana Nursruwening; Wita Widyandini; Alifia Rizky Rahma Kautsar; Nurita Iman Sari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Ornaments or generally referred to as decorative designs are art that is used with the aim of beautifying. The application of ornaments in the field of architecture, especially interiors,is widely applied to floors, ceilings, walls, openings and other interior elements. Suminagashi is a technique for making unique and beautiful ornaments where thin ink is applied to the surface of water and then transferred to cloth or paper. This technique became a very famous art from Japan because it combines unique and impressive colours. This Community Service aims to provide input and feedback on matters relating to architectural aesthetic shapes and colours using the suminagashi method on cloth media. So that this service activity provides benefits, that the community can learn design approach techniques by preserving suminagashi crafts using patterns, colours and materials by utilizing items available in the surrounding environment so that in the future it becomes a forum for creative collaboration for the community to increase productivity, develop interests and talents and the economy of the residents by bringing in other creative themes.